Diversity of Gastropoda in the Intertidal Zone of Tanjung Pinggir Beach, Batam City - Fitra, Ramadani; Winanda, Witri; Aini, Wardatul; Anwar, Khairul; Fathia, Mona; Winata, Hansen Fandy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The intertidal zone is a coastal ecosystem with high biological productivity that supports various benthic organisms, including gastropoda. Increasing anthropogenic activities in coastal areas may influence the composition and community structure of gastropoda as ecological indicators. This study aimed to analyze the species composition, density, and community structure of gastropoda in the intertidal zone of Tanjung Pinggir Beach, Batam City. The research was conducted in April 2026 using a survey method with line transect–quadrat techniques at five sampling stations. We laid out a single, 50-m long transect perpendicular to the shoreline at each site. Quadrats were placed every 10 m along this line, which resulted in five sampling units per station (n = 6 quadrats). Gastropod samples were identified morphologically, while data analyses included species composition, density, diversity index, evenness index, and dominance index. The results showed that 42 gastropod species belonging to 5 orders and 17 families were identified, with Caenogastropoda and Neogastropoda as the dominant orders. The highest gastropod density was recorded at Station 4 (5.88 ind./m²), while the lowest was found at Station 1 (0.96 ind./m²). Relative density analysis indicated that Batillaria zonalis and Batillaria attramentaria were the dominant species across most stations. Diversity and evenness indices were categorized as moderate to high, whereas the dominance index was low, indicating a relatively stable community structure. Overall, the intertidal ecosystem of Tanjung Pinggir Beach remains ecologically supportive for gastropod communities. Sustainable coastal management is recommended to minimize future anthropogenic pressures.